2015
DOI: 10.1164/rccm.201406-1108oc
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Smoking and the Incidence of Asthma in the Black Women’s Health Study

Abstract: Rationale: Evidence linking active or passive smoking to the incidence of adult-onset asthma is inconsistent with both positive and inverse associations being reported. Most previous studies of active smoking have not accounted for passive smoke exposure, which may have introduced bias.Objectives: To assess the separate associations of active and passive smoking to the incidence of adult-onset asthma in the U.S. Black Women's Health Study, a prospective cohort of African American women followed since 1995 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 40 publications
3
69
0
2
Order By: Relevance
“…This susceptibility might be explained by the fact that any air pollution effect may be masked among smokers, who may already have a higher risk of asthma [45].…”
Section: Smokingmentioning
confidence: 99%
“…This susceptibility might be explained by the fact that any air pollution effect may be masked among smokers, who may already have a higher risk of asthma [45].…”
Section: Smokingmentioning
confidence: 99%
“…Most longitudinal studies have found an increased risk of new-onset asthma among current smokers with respect to never-smokers [1,2,3,4,5,6,7], the relative risk ranging between 1.4 and 3. However, a few studies report no effect of current smoking on asthma onset [8,9,10,11], or even a protective effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…The current literature [7,10,16] reports several reasons that could bias the estimates of the smoking-asthma association and lead to discrepant reports:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying pathophysiological mechanisms include a combination of changes in the pulmonary immune system, pro-inflammatory response, and increased oxidative stress (128, 129). …”
Section: Introductionmentioning
confidence: 99%